Pyramidal traveling fronts of a time periodic diffusion equation with degenerate monostable nonlinearity - Bu, Zhen-Hui; Wang, Chen-Lu; Zhang, Xin-Tian (Electronic journal of differential equations, 2023)
This article focuses on the nonplanar traveling fronts of degenerate monostable time periodic reaction-diffusion equations in Rn with n≥3. By constructing a couple of proper supersolution and subsolution, we prove the existence of periodic pyramidal traveling front in R3 and then in Rn with n>3.